Hardiness in Student Survivors of Schizophrenia and Bipolar Disorders in Yogyakarta - Arum Prawesti; Andhita Dyorita Khoiryasdien (Badan Penerbit STIEPARI Press, 2025)
Students with mental disorders such as schizophrenia and bipolar disorder encounter significantly more complex challenges compared to individuals without such conditions, particularly when these disorders occur alongside academic demands. This study seeks to explore the resilience, or hardiness, of students in Yogyakarta who have survived schizophrenia and bipolar disorder by employing a qualitative methodology with a phenomenological approach. The participants involved one main subject living with the disorder and one significant other as an additional perspective. Data collection was carried out through in-depth interviews and subsequently analyzed thematically using Kobasa’s three dimensions of hardiness: control, commitment, and challenge. Findings indicate that the subject made efforts to regulate emotions even though self-control often fluctuated, demonstrated a consistent commitment to persistence in pursuing personal and academic objectives, and perceived difficulties as opportunities to learn and foster growth. The development of hardiness in the subject was shaped by self-awareness, the presence of supportive social networks, and accumulated life experiences that enhanced adaptability. Despite these strengths, the study revealed that the subject still faced instability in emotional management, which highlights the need for further reinforcement in maintaining stability and coping strategies. Overall, the research emphasizes that while students with schizophrenia and bipolar disorder possess the potential to develop resilience through personal and external resources, ongoing support remains crucial for sustaining their psychological well-being and academic success.